1st ISETA - International Seminar on Education, Technology, and Arts 2022 - ISETA Committee (STKIP PGRI Banjarmasin, 2022)
1st International Seminar on Education, Technology and Arts. Theme: Tailoring Education for the Future of Work Post Covid-19